Use of autologous fibrin glue in dermatologic surgery: application of skin graft and second intention healing - Moraes, Aparecida Machado de; Annichino-Bizzacchi, Joyce Maria; Rossi, Ana Beatris Rodrigues (São Paulo Medical Journal, 1998)
OBJECTIVE: To evaluate the efficiency of biological sealant, an autologous fibrin glue, in dermatological surgery. DESIGN: Randomized clinical trial. SETTING: The Dermatology Service of Hospital das Clínicas, Universidade de Campinas (UNICAMP), referral center. PATIENTS: 14 patients with malign epithelial cutaneoos tumors participated in the evaluation, each having two tumors, generally facial and symmetrical, in order to perform a comparative evaluation on the same individual. PROCEDURES: The glue was prepared beforehand with a sample of autologous blood. Surgical extirpation of the tumor was followed by grafts or second intention healing. OUTCOMES: The efficiency of the sealant was then evaluated in relation to hemostasis, adhesion, surgical time and evolution of the granulation tissue, clinically and histologically. RESULTS: Immediate hemostasis and graft adhesion, with a significant reduction of surgical time, and in the open wounds there was immediate hemostasis and a clinical increase in granulation tissue, but with no histological differences among the groups on the 7th day. CONCLUSION: It is an adjuvant resource in skin cancer surgery.